Identification of students’ misconceptions in proving onto and one-to-one function in abstract algebra using certainty response index - Muhammad Islahul Mukmin; Arini Mayan Fa'ani (Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
This research is aimed to identify students’ misconceptions in proving onto and one-to-one function in Abstract Algebra using CRI (Certainty Response Index), which is an instrument to distinguish misconceptions and errors. This research uses qualitative method. There are eighteen research participants, and they are Mathematics Education students in 3rd semester. Researcher asked participants to solve some problems related to mathematical proof. Then, participants gave score based on their belief or level of certainty. The result shows that ten students get misconceptions. They were weak in understanding the definition of onto and one-to-one function, and are not yet trained to proof onto and one-to-one function in Abstract Algebra. Further, this research also find that the errors of participants in proving mathematics are mainly influenced by errors in algebraic operation.